Wandering Spleen and Organoaxial Gastric Volvulus after Morgagni Hernia Repair: A Case Report and Review of the Literature - Noemi Cantone; Caterina Gulia; Vittorio Miele; Margherita Trinci; Vito Briganti (Case Reports in Surgery)
Wandering spleen and gastric volvulus are two rare entities that have been described in association with congenital diaphragmatic hernia. The diagnosis is difficult and any delay can result in ischemia and necrosis of both organs. We present a case of a 13-year-old girl, previously operated on for anterior diaphragmatic hernia and intrathoracic gastric volvulus, that presented to our service for a subdiaphragmatic gastric volvulus recurrence associated with a wandering spleen. In this report we reviewed the literature, analyzing the clinical presentation, diagnostic assessment, and treatment options of both conditions, in particular in the case associated with diaphragmatic hernia.